the Ufes biology exhibition: A virtual non-formal space for scientific education - Passigatti Cezar, Raphaela; Villa Dias, Larissa; Moreira da Silva, Iris; Borges Corte, Viviana; Lavanholle Ventotin, Maria (Guará Journal, 2024)
Characterized as informal educational spaces, science fairs establish a connection between the scientific and educational spheres and the community. Due to the COVID-19 pandemic, informal educational spaces were adapted to a virtual format. In this context, science fairs and exhibitions entered virtual learning communities as innovative and safe possibilities for the teaching and learning process. The study aimed to profile the audience and their perception of the online Biology Exhibition. A semi-structured questionnaire and virtual interaction indicators were used as data collection tools. The Exhibition was well-evaluated by participants, mostly undergraduate students and professors from various states across the country. A change in the audience profile was also observed regarding the in-person format of the event. Events like these are important for disseminating scientific knowledge produced at universities to society, especially at a time when they are constantly exposed to fake news. This work aims to record the virtual format of the UFES Biology Exhibition and its importance as a non-formal virtual space for scientific education, so that it becomes a possibility to think of increasingly accessible, plural and comprehensive events.
Keywords: University extension; Science fairs; Virtual events; Non-formal education; Remote teaching